2016
DOI: 10.1111/jir.12304
|View full text |Cite
|
Sign up to set email alerts
|

Boys with fragile X syndrome: investigating temperament in early childhood

Abstract: Attention difficulties commonly found in adolescents and adults with FXS appear to also be characteristic of young boys with FXS, as reflected by lower effortful control. Age-related findings concerning negative affectivity may be particularly significant, leading to improved intervention/preventative efforts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 34 publications
2
5
0
Order By: Relevance
“…In the surgency domain, infants with FXS were generally rated as less active, less likely to seek novel environmental situations, less vocally reactive, and reduced in indices of positive affect such as smiling and laughter. In the negative affect domain, we replicated previous studies suggesting negative affect is reduced low in early childhood, despite being elevated in school-aged children (Low Kapalu & Gartstein, 2016;Shanahan et al, 2008), with particularly low distress to limitations in our sample. Notably, despite lower overall levels of negative affect in young children with FXS relative to controls, previous within-group studies have reported that higher negative affect is prospectively associated with anxiety in later childhood (Tonnsen et al, 2013).…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…In the surgency domain, infants with FXS were generally rated as less active, less likely to seek novel environmental situations, less vocally reactive, and reduced in indices of positive affect such as smiling and laughter. In the negative affect domain, we replicated previous studies suggesting negative affect is reduced low in early childhood, despite being elevated in school-aged children (Low Kapalu & Gartstein, 2016;Shanahan et al, 2008), with particularly low distress to limitations in our sample. Notably, despite lower overall levels of negative affect in young children with FXS relative to controls, previous within-group studies have reported that higher negative affect is prospectively associated with anxiety in later childhood (Tonnsen et al, 2013).…”
Section: Discussionsupporting
confidence: 88%
“…First, infants with the FXpm could exhibit similar temperament profiles to those observed in older children with FXS, reflecting shared genetic vulnerabilities and qualitatively similar yet less frequent comorbid conditions in the FXpm relative to FXS (Bailey et al, 2008). From this perspective, we would expect infants with the FXpm to exhibit reduced surgency, negative affect, and regulatory capacity, paralleling previous work in older samples with FXS (Low Kapalu & Gartstein, 2016;Shanahan et al, 2008). This outcome would suggest that infants with the FXpm may benefit from similar surveillance and intervention approaches as FXS.…”
supporting
confidence: 61%
See 2 more Smart Citations
“…Mothers with infants 6–12 months of age were recruited via social media (i.e., Facebook) advertisements, local birth centers/parent–infant programs, and pamphlets distributed in locations frequented by families with infants (e.g., pediatricians, local mall, farmers market) in two Inland Northwest communities. Children with significant medical or birth complications, including infants born preterm (<37 weeks of gestation) and/or identified as developmentally delayed/disabled, were excluded, as these conditions can be expected to result in altered patterns of temperament development (e.g., Gartstein, Marmion, & Swanson, 2006; LowKapalu & Gartstein, 2016), and children experiencing such difficulties are generally not recruited for temperament-related investigations (e.g., Gartstein & Rothbart, 2003; Gartstein et al, 2018). Non-English-speaking caregivers were also excluded, as instruments utilized for the project in addition to the IBQ-R are not available in languages other than English.…”
Section: Methodsmentioning
confidence: 99%